Rancang Bangun Sistem Informasi Monitoring Magang Pada LP3l Universitas PGRI Kanjuruhan Malang - Rosanti, Elvina; Seby Dwanoko, Yoyok; Setiyaningsih, Wiji (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2025)
Internship programs are crucial in higher education, providing students with practical work experience and preparing them for professional careers. However, the internship monitoring process at LP3L Universitas PGRI Kanjuruhan Malang is still conducted manually, resulting in inefficiencies in student registration, progress tracking, and final report archiving. These manual processes often cause delays, miscommunication, and difficulties in effectively monitoring student progress. This research aims to design and develop a web-based internship monitoring system using the Prototype model and User-Centered Design (UCD) approach. The system is intended to streamline the internship process by providing a structured and automated platform for students, lecturers, and administrators. Key features of the system include online student registration, automated progress tracking, and digital archiving of final internship reports. The system is developed using the CodeIgniter framework for the backend, MySQL for database management, and Bootstrap for the user interface, ensuring a user-friendly and efficient experience. The User Acceptance Test (UAT) results indicate an average satisfaction rate of 88.60%, proving the system's effectiveness in enhancing internship management. The implementation of this system significantly improves workflow efficiency, reduces administrative burdens, and facilitates better communication among stakeholders, ultimately leading to a more structured and transparent internship process.